Perioperative chemotherapy with docetaxel, cisplatin and capecitabine (DCX) in gastro-oesophageal adenocarcinoma: a phase II study of the Arbeitsgemeinschaft Internistische Onkologie (AIO)† - Thuss-Patience, Peter; Hofheinz, Ralf-Dieter (Annals of oncology, 2012)
AbstractBackground. This prospective multicentre phase II trial assessed the feasibility and efficacy of perioperative chemotherapy with docetaxel, cisplatin a
Gesehen am 11.10.2018